Bohemia growth machine: Street art as an urban development tool in Florida. Issue 1 (1st September 2020) - Strom, Elizabeth; Kusenbach, Margarethe
Meanings and functions of street art have, in recent decades, diversified in the United States as well as globally. Today, we find street art initiatives and mural festivals in many cities, where they are applauded for fostering local development and tourism while also producing less tangible branding and marketing outcomes. Our research, based on ethnographic fieldwork and secondary data analysis in three Florida cities, suggests that street art initiatives can indeed become, in essence, handmaids to real estate development; however, the degree to which this is the case is variable, and it is by no means inevitable that the only long-term outcome will be the cultural obliteration and physical displacement of current residents. The article's analysis describes and compares mural scenes in key redeveloping neighbourhoods in three Florida cities (Tampa, St. Petersburg and Miami) that, we argue, represent a diversity, and perhaps even a trajectory, of cities' appropriation of street art as a development tool.